Preparation method of Fe-CTF-loaded photocatalytic ceramic flat sheet membrane as well as prepared product and application of Fe-CTF-loaded photocatalytic ceramic flat sheet membrane

By efficiently combining Fe-CTF composite materials on the ceramic flat film, the problem of low degradation efficiency of ceramic flat film when dealing with toxic pollutants is solved, and the dual performance of ceramic flat film and CTF material is achieved.

CN119838441AActive Publication Date: 2025-04-18CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510048943.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The existing ceramic flat films are difficult to efficiently degrade when dealing with toxic contaminants, and it is difficult to uniformly coat CTF materials on inorganic films, which limits their application in the field of membrane separation.

Method used

By injecting an aqueous solution of Fe-CTF composite material onto the surface of the ceramic flat film, vacuum filtration, drying and high-temperature calcination, the efficient combination of the CTF material and the ceramic flat film is achieved.

Benefits of technology

The bonding strength between CTF material and ceramic flat film is improved, ensuring that the material is not easy to fall off, which can not only maintain the excellent filtration performance of ceramic flat film, but also effectively degrade organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838441A_ABST
    Figure CN119838441A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of membrane filtration, and particularly provides a preparation method of a Fe-CTF-loaded photocatalytic ceramic flat sheet membrane, a prepared product and application of the Fe-CTF-loaded photocatalytic ceramic flat sheet membrane, and the preparation method comprises the following steps: injecting an aqueous solution of a Fe-CTF composite material to the surface of a blank ceramic flat sheet membrane, carrying out vacuum filtration, drying, and carrying out high-temperature calcination to obtain the Fe-CTF-loaded photocatalytic ceramic flat sheet membrane. The Fe-CTF composite material is uniformly and efficiently loaded on the ceramic flat sheet membrane, the iron and the CTF are compounded, and the calcining temperature and time are specifically adjusted, so that the CTF material and the ceramic flat sheet membrane reach relatively high bonding strength and are not easy to fall off during working, the excellent filtering performance of the ceramic flat sheet membrane can be exerted, and the ceramic flat sheet membrane can be uniformly and efficiently loaded with the Fe-CTF composite material. And the degradation performance of CTF on organic pollutants can also be exerted, and an unexpected effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of membrane filtration, and in particular to a method for preparing a Fe-CTF-loaded photocatalytic ceramic flat membrane and a product prepared therefrom and applications thereof. Background Art

[0002] my country has a large population, uneven distribution of water resources, and an increasingly serious water shortage. A large number of lakes and rivers have been polluted, further exacerbating my country's water crisis. Therefore, efficient use of water resources has become a hot topic and focus of current research. The most widely used technology in wastewater treatment and seawater desalination is membrane filtration technology.

[0003] Compared with organic membranes, inorganic membranes have excellent thermal stability and pore stability, high mechanical strength, chemical corrosion resistance, good recycling performance, and can achieve the dual effects of rapid filtration and precision filtration at the same time. As a membrane separation material with excellent performance, ceramic flat membranes have been widely used in wastewater treatment and other fields. Since there are many toxic pollutants such as organic dyes, antibiotics, phenols and heavy metal ions in wastewater, these pollutants are usually highly toxic, difficult to degrade and easy to accumulate, posing a serious threat to the ecosystem and human health. Ceramic flat membranes cannot efficiently treat and degrade these toxic pollutants. Therefore, combining photocatalytic oxidation technology with membrane separation technology has been the focus of research in recent years.

[0004] Covalent triazine frameworks (CTFs) are a class of two-dimensional layered polymers composed of aromatic rings and nitrogen-rich triazine rings as connecting units. They are widely used in the field of photocatalysis due to their high specific surface area, adjustable pore structure, suitable band gap and high chemical stability. However, due to the poor solubility of powdered CTFs, it is difficult to coat such materials uniformly and efficiently on the surface of inorganic membranes, which limits their application in the field of membrane separation. Summary of the invention

[0005] The purpose of the present invention is to solve the above problems and provide a method for preparing a Fe-CTF-loaded photocatalytic ceramic flat membrane and the products and applications thereof. The CTF material and the ceramic flat membrane in the Fe-CTF-loaded photocatalytic ceramic flat membrane achieve a high bonding strength and are not easy to fall off during operation. The excellent filtering performance of the ceramic flat membrane can be brought into play, and the degradation performance of CTF on organic pollutants can also be brought into play, achieving unexpected results.

[0006] In order to achieve the above object, the technical solution of the present invention is as follows:

[0007] A method for preparing a Fe-CTF-loaded photocatalytic ceramic flat film comprises the following steps:

[0008] Step 1, placing a blank ceramic flat membrane into a suction filtration device;

[0009] Step 2: injecting the aqueous solution of the Fe-CTF composite material onto the surface of the ceramic flat membrane under vacuum filtration;

[0010] Step 3, performing a first drying and calcining treatment on the ceramic flat membrane obtained in step 2 in sequence to obtain a Fe-CTF-loaded photocatalytic ceramic flat membrane;

[0011] The calcination temperature is not less than 400°C, and the calcination time is not less than 1 hour.

[0012] The present application provides a method for preparing a photocatalytic ceramic flat membrane loaded with Fe-CTF, wherein an aqueous solution of a Fe-CTF composite material is injected onto the surface of a blank ceramic flat membrane, and after vacuum filtration, the Fe-CTF composite material is dried and calcined at a high temperature, so that the Fe-CTF composite material can be uniformly and efficiently loaded onto the ceramic flat membrane. The present application compounds iron with CTF and specifically adjusts the calcination temperature and time, so that the CTF material and the ceramic flat membrane achieve a high bonding strength, and are not easy to fall off during operation, which can give full play to the excellent filtration performance of the ceramic flat membrane, and the degradation performance of CTF on organic pollutants, thereby achieving unexpected results.

[0013] Furthermore, in step 2, the pressure during filtration is -0.1 to -0.3 MPa.

[0014] Furthermore, in step 2, when injecting the aqueous solution of the Fe-CTF composite material onto the surface of the ceramic flat membrane, a small amount of injection is performed multiple times to avoid material loss due to too low a suction filtration speed, and the number of injections is 2-5 times.

[0015] Furthermore, in step 2, the aqueous solution of the Fe-CTF composite material is a mixed solution of the Fe-CTF composite material and water, and the concentration is 0.5 to 1 g / L.

[0016] Furthermore, the Fe-CTF composite material is prepared by the following method:

[0017] S1, mixing the CTF material with the iron salt solution and stirring;

[0018] S2. The solution obtained in S1 is subjected to suction filtration, a second drying, centrifugal washing and a third drying treatment in sequence to obtain a Fe-CTF composite material.

[0019] Furthermore, the carbon content in CTF material is: 50%-55%, nitrogen content: 15%-20%, SSA: 1400-1500m 2 / g.

[0020] Furthermore, in the aqueous solution of the Fe-CTF composite material, 0.0025-0.005 molFe is contained in every 50-60 mgCTF. Through a large number of studies by the inventors, it is found that the amount of iron added to the composite material is closely related to the photocatalytic effect and adhesion performance of the photocatalytic ceramic flat film loaded with Fe-CTF in the end. Too much or too little iron content will affect the performance of the product. Preferably, in the aqueous solution of the Fe-CTF composite material, 0.003-0.005 molFe is contained in every 50-60 mgCTF.

[0021] Furthermore, the iron salt is a ferric chloride solution or a ferric nitrate solution.

[0022] Furthermore, the concentration of the iron salt is 0.05-0.1 mol / L.

[0023] Furthermore, in step 3, the calcination temperature is 400°C to 600°C. Studies have found that the calcination temperature directly affects the photocatalytic effect and adhesion performance of the final Fe-CTF-loaded photocatalytic ceramic flat membrane. When the calcination temperature is lower than 400°C, the bonding strength of the composite material on the flat membrane will be greatly reduced, and the photocatalytic effect will also be reduced. Preferably, the calcination temperature is 500°C to 600°C.

[0024] Furthermore, in step 3, the calcination time is 1 to 2 hours. Studies have found that the calcination time directly affects the photocatalytic effect and adhesion performance of the final Fe-CTF-loaded photocatalytic ceramic flat membrane. When the calcination time is less than 1 hour, the bonding strength of the composite material on the flat membrane will be greatly reduced, and the photocatalytic effect will also be reduced.

[0025] Furthermore, in step 3, during the calcination treatment, the heating rate is 5-10°C / min.

[0026] Another object of the present invention is to provide a product prepared by the above preparation method.

[0027] The Fe-CTF-loaded photocatalytic ceramic flat membrane is prepared by the above-mentioned preparation method.

[0028] Furthermore, specifically, the Fe-CTF composite material is uniformly attached to the surface of the ceramic flat membrane, and the thickness of the Fe-CTF composite material is 0.1 to 0.3 mm.

[0029] Another object of the present invention is to provide an application of the above-mentioned Fe-CTF-loaded photocatalytic ceramic flat membrane.

[0030] The above-mentioned Fe-CTF-loaded photocatalytic ceramic flat membrane is used for photocatalytic degradation of pollutants.

[0031] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0032] The present application provides a method for preparing a photocatalytic ceramic flat membrane loaded with Fe-CTF, and the products and applications prepared therefrom. The preparation method comprises injecting an aqueous solution of a Fe-CTF composite material onto the surface of a blank ceramic flat membrane, vacuum filtration, drying, and high-temperature calcination, so that the Fe-CTF composite material can be uniformly and efficiently loaded onto the ceramic flat membrane. The present application compounds iron with CTF and specifically adjusts the calcination temperature and time, so that the CTF material and the ceramic flat membrane achieve a high bonding strength, which is not easy to fall off during operation, and can give full play to the excellent filtration performance of the ceramic flat membrane, as well as the degradation performance of CTF on organic pollutants, achieving unexpected results. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the SEM image of the Fe-doped CTF in Example 1.

[0034] Figure 2 This is the SEM image of the Fe-CTF / ceramic flat membrane in Example 1. DETAILED DESCRIPTION

[0035] The present invention will be described in detail below in conjunction with the accompanying drawings.

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] Example 1

[0038] The blank ceramic flat membrane was placed in anhydrous ethanol, ultrasonically cleaned for 30 min, and dried in an oven at 80°C for later use.

[0039] The CTF material was mixed with 0.05 mol / L ferric chloride solution and stirred on a magnetic stirrer for 1 h;

[0040] Then, the mixture was filtered, dried, centrifugally washed, and dried again to obtain a Fe-CTF composite material; wherein, every 50 mg of CTF contained 0.004 mol of Fe.

[0041] The Fe-CTF composite material was added into deionized water and fully mixed by ultrasonication for 30 min to obtain an aqueous solution with a concentration of 0.8 g / LFe-CTF composite material.

[0042] The dried ceramic flat membrane is placed in a filtration device, and the aqueous solution of the Fe-CTF composite material is injected onto the surface of the ceramic flat membrane with a syringe (when injecting the aqueous solution of the Fe-CTF composite material onto the surface of the ceramic flat membrane, multiple small injections are made to avoid material loss due to too low a filtration speed, and the number of injections is 2-5 times), and filtration is performed at a pressure of -0.1 MPa until the Fe-CTF composite material is evenly deposited on the membrane.

[0043] The filtered sample was placed in an oven at 80°C for 12 hours, and then calcined in a tubular furnace for 2 hours at a calcination temperature of 500°C and a heating rate of 5°C / min. After naturally cooling to room temperature, a photocatalytic ceramic flat film loaded with Fe-CTF was obtained.

[0044] The Fe-CTF and Fe-CTF / photocatalytic ceramic flat membranes prepared in Example 1 were characterized by SEM and Mapping. Figure 1 , Figure 2 shown.

[0045] Depend on Figure 1 , Figure 2 It can be seen that CTF is successfully doped with Fe and efficiently and evenly loaded onto the ceramic flat membrane with a loading thickness of 0.2 mm.

[0046] Example 2

[0047] The blank ceramic flat membrane was placed in anhydrous ethanol, ultrasonically cleaned for 30 min, and dried in an oven at 80°C for later use.

[0048] The CTF material was mixed with 0.05 mol / L ferric chloride solution and stirred on a magnetic stirrer for 1 h;

[0049] Then, the mixture was filtered, dried, centrifuged and washed, and dried again to obtain a Fe-CTF composite material; wherein, every 55 mg of CTF contained 0.005 mol of Fe.

[0050] The Fe-CTF composite material was added into deionized water and fully mixed by ultrasonication for 30 min to obtain an aqueous solution of the Fe-CTF composite material with a concentration of 1 g / LFe.

[0051] The dried ceramic flat membrane is placed in a filtration device, and the aqueous solution of the Fe-CTF composite material is injected into the surface of the ceramic flat membrane with a syringe (when injecting the aqueous solution of the Fe-CTF composite material into the surface of the ceramic flat membrane, multiple small injections are made to avoid material loss due to too low a filtration speed, and the number of injections is 2-5 times), and filtration is performed at a pressure of -0.2Mpa until the Fe-CTF composite material is evenly deposited on the membrane.

[0052] The filtered sample was placed in an oven at 80°C for 12 hours, and then calcined in a tubular furnace for 2 hours. The calcination temperature was 400°C and the heating rate was 8°C / min. After naturally cooling to room temperature, a photocatalytic ceramic flat film loaded with Fe-CTF was obtained.

[0053] It was detected that the thickness of the Fe-CTF composite material in the Fe-CTF-loaded photocatalytic ceramic flat membrane was 0.1 mm.

[0054] Example 3

[0055] The blank ceramic flat membrane was placed in anhydrous ethanol, ultrasonically cleaned for 30 min, and dried in an oven at 80°C for later use.

[0056] The CTF material was mixed with 0.05 mol / L ferric chloride solution and stirred on a magnetic stirrer for 1 h;

[0057] Then, the mixture was filtered, dried, centrifugally washed, and dried again to obtain a Fe-CTF composite material; wherein, every 60 mg of CTF contained 0.0025 mol of Fe.

[0058] The Fe-CTF composite material was added into deionized water and fully mixed by ultrasonication for 30 min to obtain an aqueous solution of the Fe-CTF composite material with a concentration of 0.5 g / LF.

[0059] The dried ceramic flat membrane is placed in a filtration device, and the aqueous solution of the Fe-CTF composite material is injected onto the surface of the ceramic flat membrane with a syringe (when injecting the aqueous solution of the Fe-CTF composite material onto the surface of the ceramic flat membrane, multiple small injections are made to avoid material loss due to too low a filtration speed, and the number of injections is 2-5 times), and filtration is performed at a pressure of -0.3Mpa until the Fe-CTF composite material is evenly deposited on the membrane.

[0060] The filtered sample was placed in an oven at 80°C for 12 hours, and then calcined in a tubular furnace for 1 hour at a calcination temperature of 600°C and a heating rate of 10°C / min. After naturally cooling to room temperature, a photocatalytic ceramic flat film loaded with Fe-CTF was obtained.

[0061] It was detected that the thickness of the Fe-CTF composite material in the Fe-CTF-loaded photocatalytic ceramic flat membrane was 0.3 mm.

[0062] Comparative Example 1

[0063] Comparative Example 1 Compared with Example 1, no iron element was added, and the CTF material was directly injected onto the surface of the ceramic flat membrane. The operation method and process parameters were the same as those of Example 1, and the specific ones were as follows:

[0064] The blank ceramic flat membrane was placed in anhydrous ethanol, ultrasonically cleaned for 30 min, and dried in an oven at 80°C for later use.

[0065] The CTF material was added into deionized water and thoroughly mixed by ultrasonication for 30 min to obtain an aqueous solution of CTF material with a concentration of 0.8 g / L.

[0066] Place the dried ceramic flat membrane into a filtration device, and inject the aqueous solution of CTF material onto the surface of the ceramic flat membrane with a syringe (inject the CTF aqueous solution into the surface of the ceramic flat membrane in small amounts multiple times to avoid material loss due to too low a filtration speed, and the number of injections is 2-5 times), and filter at a pressure of -0.1Mpa until the CTF material is evenly deposited on the membrane.

[0067] The filtered sample was placed in an oven at 80°C for 12 hours, and then calcined in a tubular furnace for 2 hours. The calcination temperature was 500°C and the heating rate was 5°C / min. After naturally cooling to room temperature, a photocatalytic ceramic flat film loaded with CTF was obtained.

[0068] Comparative Example 2

[0069] Comparative Example 2 is compared with Example 1, in which the iron element is replaced by manganese, and the Mn-CTF material is injected onto the surface of the ceramic flat membrane. The operation method and process parameters are the same as those of Example 1, and the details are as follows:

[0070] The blank ceramic flat membrane was placed in anhydrous ethanol, ultrasonically cleaned for 30 min, and dried in an oven at 80°C for later use.

[0071] The CTF material was mixed with 0.05 mol / L manganese chloride solution and stirred on a magnetic stirrer for 1 h;

[0072] Then, the mixture was filtered, dried, centrifuged and washed, and dried again to obtain a Mn-CTF composite material; wherein, every 50 mg of CTF contained 0.004 mol of Mn.

[0073] The Mn-CTF composite material was added into deionized water and fully mixed by ultrasonication for 30 min to obtain an aqueous solution with a concentration of 0.8 g / LMn-CTF composite material.

[0074] The dried ceramic flat membrane is placed in a filtration device, and the aqueous solution of the Mn-CTF composite material is injected onto the surface of the ceramic flat membrane with a syringe (when injecting the aqueous solution of the Mn-CTF composite material onto the surface of the ceramic flat membrane, multiple small injections are made to avoid material loss due to too low a filtration speed, and the number of injections is 2-5 times), and filtration is performed at a pressure of -0.1 MPa until the Mn-CTF composite material is evenly deposited on the membrane.

[0075] The filtered sample was placed in an oven at 80°C for 12 hours, and then placed in a tubular furnace for calcination for 2 hours. The calcination temperature was 500°C and the heating rate was 5°C / min. After naturally cooling to room temperature, a photocatalytic ceramic flat film loaded with Mn-CTF was obtained.

[0076] Comparative Example 3

[0077] Comparative Example 3 Compared with Example 1, the iron element is replaced by copper, and the Cu-CTF material is injected onto the surface of the ceramic flat membrane. The operation method and process parameters are the same as those of Example 1, and the details are as follows:

[0078] The blank ceramic flat membrane was placed in anhydrous ethanol, ultrasonically cleaned for 30 min, and dried in an oven at 80°C for later use.

[0079] The CTF material was mixed with 0.05 mol / L copper chloride solution and stirred on a magnetic stirrer for 1 h;

[0080] Then, the mixture was filtered, dried, centrifugally washed, and dried again to obtain a Cu-CTF composite material; wherein, every 50 mg of CTF contained 0.004 mol of Cu.

[0081] The Cu-CTF composite material was added into deionized water and thoroughly mixed by ultrasonication for 30 min to obtain an aqueous solution of the Cu-CTF composite material with a concentration of 0.8 g / LC.

[0082] The dried ceramic flat membrane is placed in a filtration device, and the aqueous solution of the Cu-CTF composite material is injected onto the surface of the ceramic flat membrane with a syringe (when injecting the aqueous solution of the Cu-CTF composite material onto the surface of the ceramic flat membrane, multiple small injections are made to avoid material loss due to too low a filtration speed, and the number of injections is 2-5 times), and filtration is performed at a pressure of -0.1 MPa until the Cu-CTF composite material is evenly deposited on the membrane.

[0083] The filtered sample was placed in an oven at 80°C for 12 hours, and then calcined in a tubular furnace for 2 hours at a calcination temperature of 500°C and a heating rate of 5°C / min. After naturally cooling to room temperature, a photocatalytic ceramic flat film loaded with Cu-CTF was obtained.

[0084] Comparative Example 4

[0085] Comparative Example 4 changes the calcination temperature compared to Example 1, and the operation method and process parameters are the same as those of Example 1, and the details are as follows:

[0086] The blank ceramic flat membrane was placed in anhydrous ethanol, ultrasonically cleaned for 30 min, and dried in an oven at 80°C for later use.

[0087] The CTF material was mixed with 0.05 mol / L ferric chloride solution and stirred on a magnetic stirrer for 1 h;

[0088] Then, the mixture was filtered, dried, centrifugally washed, and dried again to obtain a Fe-CTF composite material; wherein, every 50 mg of CTF contained 0.004 mol of Fe.

[0089] The Fe-CTF composite material was added into deionized water and fully mixed by ultrasonication for 30 min to obtain an aqueous solution with a concentration of 0.8 g / LFe-CTF composite material.

[0090] The dried ceramic flat membrane is placed in a filtration device, and the aqueous solution of the Fe-CTF composite material is injected onto the surface of the ceramic flat membrane with a syringe (when injecting the aqueous solution of the Fe-CTF composite material onto the surface of the ceramic flat membrane, multiple small injections are made to avoid material loss due to too low a filtration speed, and the number of injections is 2-5 times), and filtration is performed at a pressure of -0.1 MPa until the Fe-CTF composite material is evenly deposited on the membrane.

[0091] The filtered sample was placed in an oven at 80°C for 12 hours, and then placed in a tubular furnace for calcination for 2 hours. The calcination temperature was 200°C and the heating rate was 5°C / min. After naturally cooling to room temperature, a photocatalytic ceramic flat film loaded with Fe-CTF was obtained.

[0092] Comparative Example 5

[0093] Comparative Example 5 changes the calcination time compared to Example 1, and the operation method and process parameters are the same as those of Example 1, specifically as follows:

[0094] The blank ceramic flat membrane was placed in anhydrous ethanol, ultrasonically cleaned for 30 min, and dried in an oven at 80°C for later use.

[0095] The CTF material was mixed with 0.05 mol / L ferric chloride solution and stirred on a magnetic stirrer for 1 h;

[0096] Then, the mixture was filtered, dried, centrifugally washed, and dried again to obtain a Fe-CTF composite material; wherein, every 50 mg of CTF contained 0.004 mol of Fe.

[0097] The Fe-CTF composite material was added into deionized water and fully mixed by ultrasonication for 30 min to obtain an aqueous solution with a concentration of 0.8 g / LFe-CTF composite material.

[0098] The dried ceramic flat membrane is placed in a filtration device, and the aqueous solution of the Fe-CTF composite material is injected onto the surface of the ceramic flat membrane with a syringe (when injecting the aqueous solution of the Fe-CTF composite material onto the surface of the ceramic flat membrane, multiple small injections are made to avoid material loss due to too low a filtration speed, and the number of injections is 2-5 times), and filtration is performed at a pressure of -0.1 MPa until the Fe-CTF composite material is evenly deposited on the membrane.

[0099] The filtered sample was placed in an oven at 80°C for 12 hours, and then calcined in a tubular furnace for 0.5 hours. The calcination temperature was 500°C and the heating rate was 5°C / min. After naturally cooling to room temperature, a photocatalytic ceramic flat film loaded with Fe-CTF was obtained.

[0100] Comparative Example 6

[0101] Comparative Example 6 was not calcined compared to Example 1, and the details are as follows:

[0102] The blank ceramic flat membrane was placed in anhydrous ethanol, ultrasonically cleaned for 30 min, and dried in an oven at 80°C for later use.

[0103] The CTF material was mixed with 0.05 mol / L ferric chloride solution and stirred on a magnetic stirrer for 1 h;

[0104] Then, the mixture was filtered, dried, centrifugally washed, and dried again to obtain a Fe-CTF composite material; wherein, every 50 mg of CTF contained 0.004 mol of Fe.

[0105] The Fe-CTF composite material was added into deionized water and fully mixed by ultrasonication for 30 min to obtain an aqueous solution with a concentration of 0.8 g / LFe-CTF composite material.

[0106] The dried ceramic flat membrane is placed in a filtration device, and an aqueous solution of the Fe-CTF composite material is injected onto the surface of the ceramic flat membrane with a syringe (when injecting the aqueous solution of the Fe-CTF composite material onto the surface of the ceramic flat membrane, multiple small injections are made to avoid material loss due to too low a filtration speed, and the number of injections is 2-5 times), and filtration is performed at a pressure of -0.1 MPa until the Fe-CTF composite material is evenly deposited on the membrane, thereby obtaining a photocatalytic ceramic flat membrane loaded with Fe-CTF.

[0107] Comparative Example 7

[0108] Comparative Example 7 changes the composite content of iron compared to Example 1, and the operation method and process parameters are the same as those of Example 1, specifically as follows:

[0109] The blank ceramic flat membrane was placed in anhydrous ethanol, ultrasonically cleaned for 30 min, and dried in an oven at 80°C for later use.

[0110] The CTF material was mixed with 0.05 mol / L ferric chloride solution and stirred on a magnetic stirrer for 1 h;

[0111] Then, the mixture was filtered, dried, centrifuged and washed, and dried again to obtain a Fe-CTF composite material; wherein, every 50 mg of CTF contained 0.002 mol of Fe.

[0112] The Fe-CTF composite material was added into deionized water and fully mixed by ultrasonication for 30 min to obtain an aqueous solution with a concentration of 0.8 g / LFe-CTF composite material.

[0113] The dried ceramic flat membrane is placed in a filtration device, and the aqueous solution of the Fe-CTF composite material is injected onto the surface of the ceramic flat membrane with a syringe (when injecting the aqueous solution of the Fe-CTF composite material onto the surface of the ceramic flat membrane, multiple small injections are made to avoid material loss due to too low a filtration speed, and the number of injections is 2-5 times), and filtration is performed at a pressure of -0.1 MPa until the Fe-CTF composite material is evenly deposited on the membrane.

[0114] The filtered sample was placed in an oven at 80°C for 12 hours, and then calcined in a tubular furnace for 2 hours at a calcination temperature of 500°C and a heating rate of 5°C / min. After naturally cooling to room temperature, a photocatalytic ceramic flat film loaded with Fe-CTF was obtained.

[0115] Comparative Example 8

[0116] Comparative Example 8 changes the composite content of iron compared to Example 1, and the operation method and process parameters are the same as those of Example 1, specifically as follows:

[0117] The blank ceramic flat membrane was placed in anhydrous ethanol, ultrasonically cleaned for 30 min, and dried in an oven at 80°C for later use.

[0118] The CTF material was mixed with 0.05 mol / L ferric chloride solution and stirred on a magnetic stirrer for 1 h;

[0119] Then, the mixture was filtered, dried, centrifugally washed, and dried again to obtain a Fe-CTF composite material; wherein, every 50 mg of CTF contained 0.008 mol of Fe.

[0120] The Fe-CTF composite material was added into deionized water and fully mixed by ultrasonication for 30 min to obtain an aqueous solution with a concentration of 0.8 g / LFe-CTF composite material.

[0121] The dried ceramic flat membrane is placed in a filtration device, and the aqueous solution of the Fe-CTF composite material is injected onto the surface of the ceramic flat membrane with a syringe (when injecting the aqueous solution of the Fe-CTF composite material onto the surface of the ceramic flat membrane, multiple small injections are made to avoid material loss due to too low a filtration speed, and the number of injections is 2-5 times), and filtration is performed at a pressure of -0.1 MPa until the Fe-CTF composite material is evenly deposited on the membrane.

[0122] The filtered sample was placed in an oven at 80°C for 12 hours, and then calcined in a tubular furnace for 2 hours at a calcination temperature of 500°C and a heating rate of 5°C / min. After naturally cooling to room temperature, a photocatalytic ceramic flat film loaded with Fe-CTF was obtained.

[0123] test

[0124] The ceramic flat membranes loaded with materials prepared in Examples 1-3 and Comparative Examples 1-8 were subjected to photocatalytic degradation experiments and the shedding rates after use were recorded. The test results are shown in Table 1.

[0125] In the photocatalytic degradation experiment, Rhodamine B (RhB) solution was selected as the target pollutant. The specific experimental steps were as follows: the prepared photocatalytic ceramic flat membrane was placed in 50mL of 50mg / L pollutant solution, stirred to make the pollutant fully contact with the catalyst, and degraded under xenon lamp irradiation for 1h after dark adsorption for 30min. 3ml of pollutant solution was taken out at regular intervals, and the degradation effect was analyzed by ultraviolet absorption spectrum. After the photocatalytic experiment, the pollutant solution was filtered and the CTF shedding rate was analyzed.

[0126] Table 1

[0127] / Degradation rate (%) CTF shedding rate (%) Example 1 98.5 1.8 Example 2 97.2 1.5 Example 3 98.1 1.9 Comparative Example 1 59.3 6.5 Comparative Example 2 68.1 5.6 Comparative Example 3 68.6 5.2 Comparative Example 4 94.5 12.5 Comparative Example 5 95.3 13.2 Comparative Example 6 93.2 85.5 Comparative Example 7 82.8 4.2 Comparative Example 8 6.5 5.0

[0128] The present application provides a method for preparing a photocatalytic ceramic flat membrane loaded with Fe-CTF, and the products and applications prepared therefrom. The preparation method comprises injecting an aqueous solution of a Fe-CTF composite material onto the surface of a blank ceramic flat membrane, vacuum filtration, drying, and high-temperature calcination, so that the Fe-CTF composite material can be uniformly and efficiently loaded onto the ceramic flat membrane. The present application compounds iron with CTF and specifically adjusts the calcination temperature and time, so that the CTF material and the ceramic flat membrane achieve a high bonding strength, which is not easy to fall off during operation, and can give full play to the excellent filtration performance of the ceramic flat membrane, as well as the degradation performance of CTF on organic pollutants, achieving unexpected results.

[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a photocatalytic ceramic flat film loaded with Fe-CTF, characterized in that: The following steps are involved: Step 1, placing a blank ceramic flat membrane into a suction filtration device; Step 2: injecting the aqueous solution of the Fe-CTF composite material onto the surface of the ceramic flat membrane under vacuum filtration; Step 3, performing a first drying and calcining treatment on the ceramic flat membrane obtained in step 2 in sequence to obtain a Fe-CTF-loaded photocatalytic ceramic flat membrane; The calcination temperature is not less than 400°C, and the calcination time is not less than 1 hour.

2. The method for preparing a Fe-CTF-loaded photocatalytic ceramic flat membrane according to claim 1, characterized in that: In the step 2, the aqueous solution of the Fe-CTF composite material is a mixed solution of the Fe-CTF composite material and water, and the concentration is 0.5-1 g / L.

3. The method for preparing a Fe-CTF-loaded photocatalytic ceramic flat membrane according to claim 2, characterized in that: The Fe-CTF composite material was prepared by the following method: S1, mixing the CTF material with the iron salt solution and stirring; S2. The solution obtained in S1 is subjected to suction filtration, a second drying, centrifugal washing and a third drying treatment in sequence to obtain a Fe-CTF composite material.

4. The method for preparing a Fe-CTF-loaded photocatalytic ceramic flat membrane according to claim 1, characterized in that: The aqueous solution of the Fe-CTF composite material contains 0.0025 to 0.005 mol of Fe per 50 to 60 mg of CTF.

5. The method for preparing a photocatalytic ceramic flat film loaded with Fe-CTF according to claim 4, characterized in that: The aqueous solution of the Fe-CTF composite material contains 0.003 to 0.005 mol of Fe per 50 to 60 mg of CTF.

6. The method for preparing a Fe-CTF-loaded photocatalytic ceramic flat membrane according to any one of claims 1 to 5, characterized in that: In the step 3, the calcination temperature is 400°C to 600°C.

7. The method for preparing a photocatalytic ceramic flat film loaded with Fe-CTF according to claim 6, characterized in that: In step 3, the calcination time is 1 to 2 hours.

8. A photocatalytic ceramic flat membrane product loaded with Fe-CTF prepared by the preparation method according to any one of claims 1 to 7.

9. The Fe-CTF-loaded photocatalytic ceramic flat membrane product according to claim 8, characterized in that: Specifically, the Fe-CTF composite material is uniformly attached to the surface of the ceramic flat membrane, and the thickness of the Fe-CTF composite material is 0.1 to 0.3 mm.

10. Use of the Fe-CTF loaded photocatalytic ceramic flat membrane product as described in 8 or 9 in photocatalytic degradation of pollutants.

Citation Information

Patent Citations

  • Preparation method of heterogeneous Fenton-like catalyst with CTFs material as carrier

    CN115007150A

  • Covalent organic framework membranes, methods and uses thereof

    WO2023009072A2